Prediction of behaviour kinetics and toxicity of engineered nanomaterials in aqueous environment using neural networks - Ondiaka, Mary Nelima (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.